Katie sprinkled secrets - Simon, Coco (Simon, Coco. Cupcake diaries, 2015)
"Katie has a tough time keeping one secret...what happens when she has to keep four? All of the cupcake girls have secrets and are ready to burst! Katie loves knowing a secret; it's just tough for her to keep them! And in this story all her friends have told her a secret! From new crushes to someone cheating on a math test, Katie doesn't know what to do with all of this juicy information! Can the Cupcake Club survive with everyone keeping secrets from one another? The girls soon realize they need to confide in each other--after all what are best friends for if not for keeping your secrets?" --